Proceedings of the Twenty-Eighth Annual ACM-SIAM Symposium on Discrete Algorithms 2017
DOI: 10.1137/1.9781611974782.55
|View full text |Cite
|
Sign up to set email alerts
|

Minimum Fill-In: Inapproximability and Almost Tight Lower Bounds

Abstract: Performing Gaussian elimination to a sparse matrix may turn some zeroes into nonzero values, so called fill-ins, which we want to minimize to keep the matrix sparse. Let n denote the rows of the matrix and k the number of fill-ins. For the minimum fill-in problem, we exclude the existence of polynomial time approximation schemes, assuming P =NP, and the existence of 2 O(n 1−δ ) -time approximation schemes for any positive δ, assuming the Exponential Time Hypothesis. Also implied is a 2 O(k 1/2−δ ) · n O(1) par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…A polynomial time approximation scheme (PTAS) is a polynomial time algorithm that takes a parameter and produces an approximate solution for a minimization problem with approximation ratio . Recently, Cao and Sandeep (2017) proved that if the problems of minimizing the fill or the total number of edges in the filled graph has a PTAS, then .…”
Section: Other Approximation Algorithms In Cscmentioning
confidence: 99%
“…A polynomial time approximation scheme (PTAS) is a polynomial time algorithm that takes a parameter and produces an approximate solution for a minimization problem with approximation ratio . Recently, Cao and Sandeep (2017) proved that if the problems of minimizing the fill or the total number of edges in the filled graph has a PTAS, then .…”
Section: Other Approximation Algorithms In Cscmentioning
confidence: 99%
“…Recently, Manurangsi showed inapproximability results for maximum biclique problems, minimum k-cut, and densest at-least-k-subgraph [8]. In [9], Wu et al (2014) showed under SSEH that there are no constant factor approximation algorithms for cut, path, tree-widths, minimum fill-in (it has recently been shown that minimum fill-in has no polynomial time approximation scheme unless P = NP and that assuming ETH, there is some positive ε such that no algorithm can find a (1 + ε) approximation in time 2 O(n 1−δ ) for any positive constant δ [10]), one-shot black pebbling costs, and other problems. Those were the first results showing the hardness of constant factor approximation for these graph parameters.…”
Section: Introductionmentioning
confidence: 99%